Customer satisfaction factors at rumah sehat oxy Cirebon - Setiadi, Daryono (Universitas Wiralodra, 2023)
Water a very important role for the human body to help the body's metabolic processes, where the body needs fluid intake. In the case of Rumah Sehat OXY (RSO)/ Stockist acting as a seller of Bottled Drinking Water products with the brand OXGNDW or better known as OXY. Demanded to make customers feel satisfied by providing better offers and services. The purpose of this study is to determine consumer satisfaction based on; product quality, service quality, consumer emotionality, product price and cost of accessing price. The research method uses a quantitative descriptive technique with the research object at RSO Cirebon. The research results are based on; product quality is in the satisfactory category, service quality is quite satisfactory, the consumer's emotionality is satisfactory, the product price is satisfactory and the cost of accessing the product is satisfactory. Customer satisfaction based on service quality must be improved in terms of speed and responsiveness, good communication in providing services to customers can provide comfort in consulting. Improvement of physical facilities, especially adequate parking lots so that customers feel comfortable and places that are easily accessible to customers so that customers have no difficulty accessing